Fast spectral source integration in black hole perturbation calculations - Hopper, Seth; Forseth, Erik; Osburn, Thomas; Evans, Charles R. (Physical review. D, Particles, fields, gravitation, and cosmology, 2015)
This paper presents a new technique for achieving spectral accuracy and fast computational performance in a class of black hole perturbation and gravitational self-force calculations involving extreme mass ratios and generic orbits. Called spectral source integration (SSI), this method should see widespread future use in problems that entail (i) a point-particle description of the small compact object, (ii) frequency domain decomposition, and (iii) the use of the background eccentric geodesic motion. Frequency domain approaches are widely used in both perturbation theory flux-balance calculations and in local gravitational self-force calculations. We believe the method will extend to work for inspirals on Kerr and will be the subject of a later publication. SSI borrows concepts from discrete-time signal processing and is used to calculate the mode normalization coefficients in perturbation theory via sums over modest numbers of points around an orbit. A variant of the idea is used to obtain spectral accuracy in a solution of the geodesic orbital motion.